Development of Electronic Modules Based on Collaborative Problem Solving on Buffer Solution Materials - Andi Kurnia Sari Kadir; Dyah Purwaningsih (Postgraduate, University of Mataram, 2024)
The aim of developing an electronic module based on Collaborative Problem Solving is to determine the characteristics and quality of an e-module based on Collaborative Problem Solving on buffer solution material. This research is motivated by the lack of learning processes that utilize e-learning; one e-learning application is electronic modules based on Collaborative Problem Solving. This development research design uses the 4-D model, namely Define, Design, Develop, and Disseminate. The type of data obtained is qualitative data, which contains interview results, comments, suggestions, or input regarding the development of electronic modules. In contrast, quantitative data is obtained using questionnaire scores, which include four categories, namely strongly agree, agree, disagree, and strongly disagree. The quality of electronic modules is assessed based on expert assessments, chemistry teacher assessments, and student assessments. The results of the expert assessment were 96%, the Quality Assessment by the Chemistry Teacher was 86.77%, and the Student Assessment was 81.94%, obtaining very high validity results, so it can be concluded that the development of electronic modules can be used in schools on buffer solution materials.